Carbon/nitrogen metabolism and stress response networks - calcium-dependent protein kinases as the missing link? - Alves, Hugo L S (Journal of experimental botany, 2021)
© The Author(s) 2021. Published by Oxford University Press on behalf of the Society for Experimental Biology.